A COMPREHENSIVE STUDY ON MBG (MAKAN BERGIZI GRATIS) IN THE PRABOWO-GIBRAN CABINET: EVALUATING THE PSYCHOLOGICAL AND HEALTH IMPACTS OF THE POLICY ON UNDERSERVED COMMUNITIES - Cahyati Teguh Pancani, Peni; Ningsih, Nurna (Lafadz Jaya Publisher, 2025)
The Makan Bergizi Gratis (MBG) initiative, launched under the Prabowo-Gibran cabinet, aims to tackle food insecurity and malnutrition in Indonesia by providing free nutritious meals to underserved populations. This study evaluates the impact of the MBG program on both physical health and psychological well-being, focusing on how access to free, balanced meals influences the health and mental health outcomes of beneficiaries. A mixed-methods approach was used, combining qualitative interviews with stakeholders, quantitative health data, and psychological assessments of MBG recipients. The results indicate significant improvements in physical health, including reductions in malnutrition rates, stunting, and underweight, particularly among children. Furthermore, the study finds that MBG positively impacts psychological well-being by reducing anxiety, alleviating stress related to food insecurity, and enhancing self-esteem. Participants reported feeling more secure and less stressed about their daily nutrition, which translated into improved mood and cognitive function. However, logistical challenges, such as distribution delays and quality control, remain obstacles to the program’s widespread effectiveness. The study also underscores the importance of integrating psychological support services with nutritional assistance to maximize the program’s holistic impact. Overall, the MBG initiative has proven to be a promising model for improving both physical health and mental well-being, providing insights for other nations grappling with food insecurity and malnutrition.